Managing across Borders: An Empirical Assessment of the Bartett and Ghoshal (1989) Organizational Typology - Leong, Siew Meng (Institutional Knowledge at Singapore Management University, 1993)
An empirical test of the Bartlett and Ghoshal (1989) organizational typology is presented. One hundred thirty-one senior executives of corporations with worldwide operations classified their operations, using the Bartlett and Ghoshal typology, as being one of the following: 1. a multinational corporation, 2. a global corporation, 3. an international corporation, or 4. a transnational corporation. The executives also evaluated their organizations' configuration of assets and capabilities, role of overseas operations, and development and diffusion of knowledge. Transnational corporations, those characterized as seeking to be globally competitive through multinational flexibility and worldwide learning capability, were least frequently reported by the respondents. The hypothesized practices associated with multinational and global organizations were more consistent with the typology's predictions relative to those of the international and transnational types.